LELAGON LESTARI BUDAYAKU: GENDING PROPAGANDA BERBASIS SLOGAN - Raharja; Asep Saepudin; Siswati Siswati (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2025)
Lelagon Lestari Budayaku  is a musical composition created as one of the selected pieces for the “2023 Inter-Regency/City Yogyakarta Women's Karawitan Festival". The idea is based on the slogan "building a spirit of togetherness in cultural preservation". Based on the function and meaning contained in its lyrics, it falls into the category of propaganda music/songs. This research aims to uncover the background of its creation, methods, strategies, and stages in the process. As implied by the title of the piece, its compositional method prioritizes the aesthetics of traditional karawitan. A common challenge composers face in arranging musical pieces is the opportunity for development. A given musical form is sometimes considered fixed, making it difficult for composers to innovate creatively. For this reason, the lelagon was created in a simple form, allowing festival participants to develop a number of musical innovations. The strategic analysis applied to predict its success used the reception method. Success indicators can be seen from the percentage of participants who preferred the song and the number of views on various platforms where the video recordings were uploaded.